Inhibition of Eukaryotic Translation by the Antitumor Natural Product Agelastatin A. Issue 5 (18th May 2017) - McClary, Brandon; Zinshteyn, Boris; Meyer, Mélanie; Jouanneau, Morgan; Pellegrino, Simone; Yusupova, Gulnara; Schuller, Anthony; Reyes, Jeremy Chris P.; Lu, Junyan; Guo, Zufeng; Ayinde, Safiat; Luo, Cheng; et al.
Summary: Protein synthesis plays an essential role in cell proliferation, differentiation, and survival. Inhibitors of eukaryotic translation have entered the clinic, establishing the translation machinery as a promising target for chemotherapy. A recently discovered, structurally unique marine sponge-derived brominated alkaloid, (−)-agelastatin A (AglA), possesses potent antitumor activity. Its underlying mechanism of action, however, has remained unknown. Using a systematic top-down approach, we show that AglA selectively inhibits protein synthesis. Using a high-throughput chemical footprinting method, we mapped the AglA-binding site to the ribosomal A site. A 3.5 Å crystal structure of the 80S eukaryotic ribosome from S. cerevisiae in complex with AglA was obtained, revealing multiple conformational changes of the nucleotide bases in the ribosome accompanying the binding of AglA. Together, these results have unraveled the mechanism of inhibition of eukaryotic translation by AglA at atomic level, paving the way for future structural modifications to develop AglA analogs into novel anticancer agents. Graphical Abstract: Highlights: The antitumor natural product AglA preferentially inhibits protein synthesis AglA inhibits translation elongation and termination Binding of AglA to the A site is accompanied by conformational changes in ribosome The target of AglA is validated by a crystal structure of the AglA-ribosome complex Abstract : The natural product AglA possesses promising antitumor activity. But its mechanism of action has remained a mystery. McClary et al. identified the A site of the ribosome as the molecular target of AglA, elucidating its molecular mechanism of action.